2022
DOI: 10.1124/dmd.122.000882
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin and its Metabolites Alter mRNA of Multiple Enzyme and Transporter Genes In Vitro, but Downregulation of Organic Anion Transporting Polypeptide Does Not Translate to the Clinic

Abstract: Isotretinoin ] is widely used for the treatment of neuroblastoma and acne. It acts via regulating gene transcription through binding to retinoic acid receptors. Yet, the potential for isotretinoin to cause transcriptionally mediated drug-drug interactions (DDIs) has not been fully explored. We hypothesized that isotretinoin and its active metabolites all-transretinoic acid (atRA) and 4-oxo-13cisRA would alter the transcription of enzymes and transporters in the human liver via binding to nuclear receptors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…A previous study showed that UGT2B isoforms, including UGT2B4, UGT2B7, UGT2B15 and UGT2B17, are primarily responsible for the glucuronidation of DX to dextrorphan‐O‐glucuronide, suggesting the change in urinary MR may be due to induction of these UGTs 40 . UGT1A1 was found to be induced by approximately 2‐fold with treatment with retinoids (30 μM at RA, 13‐ cis RA or 4‐oxo‐13‐ cis RA) in human hepatocytes 41 . Another in vitro study indicated that vitamin A (100 μM) competitively inhibits UGT1A1, UGT2B4, UGT2B7 and UGT2B15 activity 42 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous study showed that UGT2B isoforms, including UGT2B4, UGT2B7, UGT2B15 and UGT2B17, are primarily responsible for the glucuronidation of DX to dextrorphan‐O‐glucuronide, suggesting the change in urinary MR may be due to induction of these UGTs 40 . UGT1A1 was found to be induced by approximately 2‐fold with treatment with retinoids (30 μM at RA, 13‐ cis RA or 4‐oxo‐13‐ cis RA) in human hepatocytes 41 . Another in vitro study indicated that vitamin A (100 μM) competitively inhibits UGT1A1, UGT2B4, UGT2B7 and UGT2B15 activity 42 .…”
Section: Discussionmentioning
confidence: 98%
“…40 UGT1A1 was found to be induced by approximately 2-fold with treatment with retinoids (30 μM atRA, 13-cisRA or 4-oxo-13-cisRA) in human hepatocytes. 41 Another in vitro study indicated that vitamin A (100 μM)…”
Section: Discussionmentioning
confidence: 99%